Bilingual partners turn into bilingual parents : reporting on decisions and consequences - Stępkowska, Agnieszka (Penerbit Universiti Kebangsaan Malaysia, 2022)
The article aims to contribute to our understanding of bilingual couples’ language choices with regard to childrearing in the less studied Polish setting. Bilingual partners often rethink their communication patterns when faced with the perspective of parenthood. A qualitative study featuring 24 in-depth interviews was conducted with linguistically mixed couples of Poles and non-Poles who represented 22 nationalities and came from six continents. In total, the target couples communicated in seven languages, including Polish. The duration of their relationships ranged from one year to over thirty. By adopting the conceptual framework of the Family Language Policy, the study identified types of bilingual families in Poland by showing that they share parallel educational experiences. Results showed no major differences in the appreciation of bilingual couplehood in the context of their children’s linguistic future and overall satisfactory evaluations of their bilingual performance. However, the analysis of interview extracts revealed differences found in parental attitudes towards the strategies of bilingual upbringing and in the reactions of children as described by the bilingual couples. The most satisfactory evaluations of the parents dissembled their once higher expectations regarding their children’s linguistic performance. There were also differences in the reported sources of knowledge about how to successfully raise a child in two languages. This indicates that the identification of parenting styles and the ensuing experiences have a crucial bearing for the understanding of bilingual communication between parents and children.